Association of dietary oxidative balance score and sleep duration with the risk of mortality: prospective study in a representative US population - Jingchu Liu; Wenjie Wang; Ying Wen (Cambridge University Press, 2023)
Abstract Objective: We investigated the association between dietary oxidative balance score (DOBS) and mortality and whether this association can be modified by sleep duration. Design: We calculated DOBS to estimate the overall oxidative effects of the diet, with higher DOBS reflecting more antioxidant intake and less pro-oxidant intake. Cox proportional hazards models were employed to examine the associations between DOBS and all-cause, CVD and cancer mortality in the general population and people with different sleep durations. Setting: Prospective analysis was conducted using data from the US National Health and Nutrition Examination Survey (NHANES, 2005-2015). Participants: A total of 15 991 US adults with complete information on dietary intake, sleep duration and mortality were included. Results: During a median follow-up of 7·4 years, 1675 deaths were observed. Participants in the highest quartile of DOBS were significantly associated with the lower risk of all-cause mortality (hazard ratio (HR) = 0·75; 95 % CI 0·61, 0·93) compared with those in the lowest. Furthermore, we found statistically significant interactions between DOBS and sleep duration on all-cause mortality (P interaction = 0·021). The inverse association between DOBS and all-cause mortality was significant in short sleepers (HR = 0·66, 95 % CI 0·48, 0·92), but not in normal and long sleepers. Conclusions: Our study observed that higher DOBS was associated with lower all-cause mortality, and this association appeared to be stronger among short sleepers. This study provides nutritional guidelines for improving health outcomes in adults, especially for short sleepers.